2013
DOI: 10.1007/s12032-013-0621-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of legumain as a potential prognostic factor on gastric cancers

Abstract: Although legumain has been found to be a prognostic factor in both breast cancer and colorectal cancer, its effects on gastric cancer are unknown. In this study, we investigated effects of legumain on gastric cancer and the correlation between legumain expression and prognosis of gastric cancer patients. SGC7901 cells were transduced with legumain cDNA (SGC7901-hLeg) for overexpression of legumain or with legumain shRNA to knock down legumain. In vitro tumor migration was examined by wound healing assay. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 23 publications
3
43
0
Order By: Relevance
“…Under physiological conditions, legumain is primarily expressed in kidney tubuli and contributes to renal tubular reabsorption 20,21 . Results of several studies have indicated that legumain expression is upregulated in a variety of different solid tumour types to a level that is positively correlated with the potential of malignancy [22][23][24] . As well as tumour cells themselves, several other cell types in the tumour-associated microenvironment have also been reported to express high levels of legumain, especially TAMs 14,16 .…”
mentioning
confidence: 99%
“…Under physiological conditions, legumain is primarily expressed in kidney tubuli and contributes to renal tubular reabsorption 20,21 . Results of several studies have indicated that legumain expression is upregulated in a variety of different solid tumour types to a level that is positively correlated with the potential of malignancy [22][23][24] . As well as tumour cells themselves, several other cell types in the tumour-associated microenvironment have also been reported to express high levels of legumain, especially TAMs 14,16 .…”
mentioning
confidence: 99%
“…This is similar to some previous reports. 10 This result might suggest AEP would be a prognostic biomarker in EOC. And based on this hypothesis, we detected that the high expression of AEP could enhance the ability of SKOV3ip cells progression both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 87%
“…11,13,21,22 AEP has recently captured the attention of researchers since some reports have identified that it is expressed higher in many solid tumor tissues compared with normal tissues. 9,10 Moreover, some studies have reported that AEP was related to tumor cell proliferation. 8,23 And blocking of AEP with antibody was reported to inhibit tumor progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AEP overexpression was observed in some solid tumors, such as breast cancer, colon cancer, lung cancer, and acute lymphoblastic leukemia [914]. The expression of AEP was higher in gastric cancer than that in the normal gastric mucosa, and AEP was an independent prognostic factor of gastric cancer [1516]. However, the mechanism by which AEP promotes invasion and metastasis in gastric cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%